Recurrent metastatic primary inflammatory myofibroblast tumour of the gallbladder following pancreaticoduodenectomy. Issue 2 (10th February 2020) - Anteby, Roi; Sullivan, Brianne J; Mani, Malary; Golas, Benjamin
Abstract : Inflammatory myofibroblast tumour (IMT) is an uncommon soft tissue tumour with an unpredictable clinical course: mostly benign, occasionally locally aggressive and rarely capable of metastasis. Diagnosed mainly in the mesentery, omentum, retroperitoneum, pelvis and lungs, IMT is extremely rare as a primary gallbladder tumour. Despite improved radiographical capabilities, differentiating the tumour from other more common causes of gallbladder neoplasms necessitates histopathological and immunohistochemistry tests. Once diagnosed, malignant potential should be taken into consideration, striving for an en bloc R0 resection and postoperative long-term follow-up with routine ancillary imaging. The authors present the case of a recurrent primary IMT of the gallbladder, after two surgical treatments, including a pancreaticoduodenectomy. Now 3 years after initial diagnoses the patient is asymptomatic, but has developed local and distant metastases and is being treated with systemic corticosteroid.